Translation of the concept «sin» in work of M. Zhumabayev «The sin of Sholpan» (Eurasian Journal of Philology Science and Education, 2016)
This article discusses the notion of concept in art works, the value of the sphere of concepts and linguistic view of the world. The research of the conceptual system of the work of Magzhan Zhumabayev «The Sin of Sholpan», regularities of functioning of concepts in the text and specifics of their reproduction in translation is conducted. Currently, the development of translation theory is characterized by numerous attempts of scientists to rethink the traditional methods of the translation process and define a new way of translation from cognitive approach. The cognitive aspect of translation is poorly studied yet and represents undoubted interest in modern linguistics and theory of translation. Background is necessary for defining the most effective translation strategy at reproduction of this or that type of information in the text. The notion of «concept» takes the central place in cognitive linguistics, cultural linguistics, translation theory and some other sciences. In the context of cognitive activity translation is the interaction of two different cognitive structures of the author and recipient through the translator’s cognition.
Keywords: concept; cognitive aspect; translation work; individual style; associative area; communicative significance.